2006
DOI: 10.1007/s00253-006-0549-5
|View full text |Cite
|
Sign up to set email alerts
|

An acetoin-regulated expression system of Bacillussubtilis

Abstract: An expression system, which is based on the promoter of the acoABCL operon of Bacillus subtilis was developed and characterized. The acoABCL operon codes for the acetoin dehydrogenase complex, which is the major enzyme system responsible for the catabolism of acetoin in B. subtilis. Besides weak organic acids, the neutral overflow metabolite acetoin is metabolized by the cells in the early stationary phase. Transcription of reporter gene fusions with the acoA promoter of this operon is strongly repressed by gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…1B). This secondary growth phase is probably caused by the utilization of overflow metabolites, such as acetoin, after the disappearance of glucose (13). After the cessation of the secondary growth phase, there is a period of Ϸ10 h during which there is no cell growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). This secondary growth phase is probably caused by the utilization of overflow metabolites, such as acetoin, after the disappearance of glucose (13). After the cessation of the secondary growth phase, there is a period of Ϸ10 h during which there is no cell growth.…”
Section: Resultsmentioning
confidence: 99%
“…Because spore formation is a long and energy-intensive process, it is plausible that sporulating cells use the overflow metabolites to complete this cell fate. The induction of overflow metabolism can be monitored by following the expression of the acetoin catabolic pathway (acoA-L), which is exclusively activated when the growth medium is exhausted for glucose (13). Indeed, we found that all cells in a microcolony express this operon at the end of the logarithmic growth phase (SI Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This assignment was based on a slight decrease in the rate of acetoin reutilization in a ytrA operon deletion. However, the ytrA operon was not induced by acetoin (45), and subsequent studies indicate that acetoin catabolism is determined by the carbon metabolite-repressed and acetoin-inducible acoABCL operon (1,35,41). Conversely, induction of the ytrA operon was noted in previous global analyses of antibiotic stress responses, and ytrA was even proposed as a reporter for glycopeptide antibiotics (18).…”
mentioning
confidence: 99%
“…It is unknown whether YtrBCDEF acts as one integrated or two separate ABC transport systems (32,45). Although initially suggested to encode an uptake system for acetoin, based on a modest decrease in acetoin utilization in a mutant strain (45), more recent studies indicate that acetoin catabolism is determined by the acetoin-inducible acoABCL operon (35,41). Moreover, acetoin does not induce ytrA expression (45).The ywoBCD operon encodes a protein of unknown function, a cysteine hydrolase, and an MFS family major facilitator transporter, respectively.…”
mentioning
confidence: 99%
“…Screening approaches are being performed to rapidly identify enzymes with potential industrial application (Korf et al, 2005). For this purpose, different expression hosts (Esherichia coli, Bacillus sp., Sacharomyces cerevisae, Pichia pastoris) have been developed to express heterologous proteins (Chelikani, Reeves, Rajbhandary, & Khorana, 2006;Silbersack et al, 2006;Li et al, 2007).…”
Section: Introductionmentioning
confidence: 99%